INTEGRATING GUSJIGANG VALUES INTO SOCIAL STUDIES EDUCATION: A QUALITATIVE STUDY ON HABITUATION AND SOCIOCULTURAL IDENTITY CONSTRUCTION IN ISLAMIC ELEMENTARY SCHOOLS - Elya Umi Hanik; Maemonah Maemonah (JMIE (Journal of Madrasah Ibtidaiyah Education), 2026)
This study aims to analyze the process of habituation of local wisdom values of Gusjigang in Social Studies learning in Madrasah Ibtidaiyah as an effort to strengthen students' socio cultural identity. This study adopts a qualitative approach field research involving classroom observations, document analysis, and in depth interviews with Social Studies teachers and fourth-grade students at Madrasah Ibtidaiyah. Data were analyzed using an interpretive qualitative framework, focusing on thematic patterns aligned with Berger and Luckmann’s stages of social construction.. Furthermore, this study identifies three stages of identity formation according to Peter and Beger's social reconstruction theory.The findings of this study indicate that the integration of Gusjigang not only enriches social studies learning but also serves as a medium for constructing socio-cultural identity. This study highlights the relevance of local wisdom in education and provides theoretical insights into the role of habituation and social construction in character formation. The novelty of this study lies in its process oriented analysis of value habituation, rather than merely evaluating learning outcomes. By applying Berger and Luckmann’s social construction theory, this research provides new insights into how local wisdom values are socially constructed, institutionalized, and internalized within daily learning practices. Theoretically, this study contributes to the literature by extending the application of social construction theory to the field of Social Studies education and local wisdom based character formation in Islamic elementary schools. Practically, the findings offer an operational framework for teachers and schools to integrate local wisdom through habituation strategies embedded in curriculum design and classroom culture